Safety of Using Contrast Agents in Coronary Angiography in a Multidisciplinary Hospital in Volgograd - V. I. Petrov; A. A. Kudasheva (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
Contrast-induced nephropathy (CIN) is a serious adverse reaction to contrast agents used in radiography. It is important to study the epidemiology of CIN and the risk factors for developing the complication in order to improve the quality of care that patients receive during coronary interventions.The aim of the study was to investigate the incidence of CIN after coronary angiography (CAG) with iopromide and analyse the cost-effectiveness of using this contrast agent in a multidisciplinary hospital in Volgograd.Materials and methods. The first part of the study comprised a medical record review of 147 patients having undergone coronary interventions (CAG and its combinations with balloon angioplasty and stenting) in the cardiology department from September 2020 to October 2021. The review involved identifying CIN cases by serum creatinine changes, assigning CIN risk scores, and assessing the volume of the contrast agent used. The second part of the study included calculating the expenses of the hospital for purchasing the contrast agent, both in total and in average per CAG procedure.Results. Having analysed serum creatinine changes, the authors identified CIN in 46 (31.3%) of CAG patients. According to Mehran risk scores for developing CIN, the baseline risk was high in 4 (2.7%) patients, moderate in 35 (23.8%) patients, and low in 108 (73.5%) patients. On average, a CAG procedure used 126.19 ± 36.35 mL of the contrast agent. The volume of the contrast agent exceeded 100 mL in 66 (44.9%) patients and the maximum acceptable contrast dose (MACD) in 8 (5.4%) patients. The MACD values were calculated using R.J. Cigarroa's formula. The average cost of a CAG procedure amounted to 1927.8 rubles.Conclusions. The authors identified CIN in one third of the CAG patients, and the highest incidence was observed in patients with diabetes mellitus and a high risk according to the Mehran score. The risk of developing CIN increased upon exceeding the maximum acceptable volume of the contrast agent. To reduce the risk of CIN, the authors recommend including MACD calculation using R.J. Cigarroa's formula and risk assessment using the Mehran score in percutaneous coronary intervention protocols.